RAND Survey of Compensation for Accidental Injuries in the United States, August 1987-August 1988 - Hensler, Deborah R. ([Verlag nicht ermittelbar], 2001)
This survey was conducted in 1989 to look at the consequences of injuries that had occurred within the past year. The main purpose was to examine medical treatment, activity restriction, loss reimbursement, and decisions regarding liability claims related to accidental injuries. Work-related stress and injuries that were fatal, resulted in institutionalization, or were caused by pharmaceutical products were not included. Questions were posed regarding treatment following the accident, resulting impairment, rehabilitation expenditures, tort liability payment, insurance benefits, expected claims, and legal assistance, along with psychological and social consequences from making the claims. While many features of this study are comparable to both the Current Population Survey (CPS) and the National Health Interview Survey (NHIS), the RAND survey is different in that questions regarding liability-claiming behaviors were asked over the course of a year, and questions about visits to care providers were included. Demographic information on respondents consists of sex, age, and education.